2018
DOI: 10.1007/s10921-018-0507-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep Scatter Estimation (DSE): Accurate Real-Time Scatter Estimation for X-Ray CT Using a Deep Convolutional Neural Network

Abstract: X-ray scatter is a major cause of image quality degradation in dimensional CT. Especially, in case of highly attenuating components scatter-to-primary ratios may easily be higher than 1. The corresponding artifacts which appear as cupping or dark streaks in the CT reconstruction may impair a metrological assessment. Therefore, an appropriate scatter correction is crucial. Thereby, the gold standard is to predict the scatter distribution using a Monte Carlo (MC) code and subtract the corresponding scatter estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 39 publications
(48 reference statements)
1
109
0
Order By: Relevance
“…Therefore, we recently proposed the deep scatter estimation (DSE) for medical CT and industrial CT . To estimate scatter, DSE uses a deep convolutional neural network which is trained to reproduce the output of MC simulations given only a function of the acquired projection data as input.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we recently proposed the deep scatter estimation (DSE) for medical CT and industrial CT . To estimate scatter, DSE uses a deep convolutional neural network which is trained to reproduce the output of MC simulations given only a function of the acquired projection data as input.…”
Section: Introductionmentioning
confidence: 99%
“…The scatter‐only or scatter‐free projections are not attainable in CBCT experiments. Available solutions are to use projections calculated by pre‐evaluated MC simulations, to use higher quality images like fan‐beam CT images or to apply image‐to‐image translation networks with unsupervised learning . Our MC simulation setups were referenced from specifications of a real CBCT machine, but the FPD grid was not considered because the data were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to medical imaging, various CNN models have been developed for low‐dose fan‐beam CT image restoration, MR‐to‐CT image symthesis, PET image segmentation, and so on . Recently, Maier et al proposed a CNN‐based scatter correction for industrial CBCT applications, and Hansen et al demonstrated that CNN‐based CBCT intensity correction improved photon dose distribution calculation accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the quality of CT reconstruction based on sub-optimal data, an ever increasing number of advanced computational approaches are being developed. Such methods include: model based and empirical beam hardening corrections [9][10][11][12], statistical noise models [13], regularized reconstructions [14], machine learning-based approaches [15,16] and approaches based on hardware calibration [17].…”
Section: Introductionmentioning
confidence: 99%